ANALISIS KELULUSAN PELAMAR KERJA DI CV. MULTINDO PRIMA TEKNIK MENGGUNAKAN ALGORITMA KLASIFIKASI - A. Serlina; Cindy Azra Salsabila; Asslia Johar Latipah (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2023)
The Naïve Bayes method is used to analyze potential job applicants' permission to enter a CV. Multindo Prima Teknik by calculating the equation for each criterion. The problem that often arises is the inefficient use of the methods used for job applicants so that they do not meet the standards and technical skills desired by the company. The Naïve Bayes method is a data mining classification approach. The aim of this research is to assess the accuracy of the Naive Bayes method using Correctly Classified Instance calculations. In this research, the Rapid Miner tool was used to test the Naïve Bayes method. The Naïve Bayes method produced an accuracy rate of 81.40% from 43 training data that was successfully evaluated, with a recall percentage of 78.95% and a precision percentage of 87.50%.